Kinetics of Oxidation of Penta-1-nol and Penta-2-nol with Chromium(VI) Influence of Some Metal Ions and Ligands - Mali, M.R.; Khodaskar, S.N.; Patel, N.T. (Asian Journal of Chemistry, 2016)
Kinetics of oxidation of penta-1-nol and penta-2-nol by chromic acid in presence of metal ions like Mn(II), Fe(II) and complexing ligands like EDTA, salicylic acid, phthalic acid and oxalic acid in acetic acid-water mixture in H2SO4 medium have been studied. The rate of reaction decreases by addition of metal ions and complexing agents like salicylic and phthalic acid, but it increases by addition of oxalic acid and EDTA.